HUBUNGAN PENGETAHUAN IBU BALITA TENTANG GIZI BALITA DENGAN STATUS GIZI BALITA DI RW 07 KELURAHAN DAYEUH LUHUR WILAYAH KERJA PUSKESMAS BENTENG KOTA SUKABUMI : Related Knowledge Mother Children About Children Nutrition with Nutritional Status of Children in RW 07 Dayeuh Luhur Work Area Puskesmas Bentenng Sukabumi City - Hana Haryani (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2020)
Malnutrition affects nearly 15% of the population and mostly from developing countries. The children are the ones who often suffer malnutrition. The purpose of this study was to determine the relationship of knowledge mother of toddler nutrition with nutritional status of children under five in RW 07 Dayeuh Sublime Work Area Health Center Fort Sukabumi. This type of research is kolerasional. The study population was as much as 131 mothers and 99 samples taken maternal, Slovin calculated by the formula. Validity test showed there were 26 valid items, and reliability values obtained r =0,789. Hypothesis testing using Shomer's formula with p-value =0,026. The results showed the majority of knowledge mother included in both categories as much as 92,6%, and toddlers with good nutritional status as much as 90,9%. Based on the results of the study there is a relationship between maternal knowledge about toddler nutrition toddler with nutritional status of children. The conclusion of this study is known the better knowledge of the mother, the more toddlers with good nutritional status, and health centers are expected to improve educational programs and nutritional enhancement.